Methods in biomedical informatics : a pragmatic approach - Sarkar, Indra Neil (Amsterdam : Elsevier/AP, Academic Press is an imprint of Elsevier, 2014)
Seeking to cross the bridge among overview, theory, and practice, this book incorporates both methodological approaches and their potential application in the domains associated with biomedical informatics.The multi-contributor book is useful for (1) those coming from a domain seeking biomedical informatics approaches for addressing specific needs; and, (2) current biomedical informaticians seeking a foundational background for methods that might be utilized in practical scenarios germane to their ongoing research.A unique characteristic of the text is its balance between foundational coverage of core topics in biomedical informatics with practical "in-the-trenches" scenarios. Contributors represent leading experts from the biomedical informatics field: individuals who have demonstrated effective use of methodology in real-world, high-quality data applications. Contains appendices that function as primers on: (1) Unix; (2) Ruby; (3) Databases; and (4) Web Services.--
Includes bibliographical references and index.
Keywords: Bioinformatics; Medical informatics; Medical Informatics -- methods; Bioinformatics; Medical informatics